First International Workshop on Emerging Trends in FLOSS Research and Development (FLOSS'07: ICSE Workshops 2007) 2007
DOI: 10.1109/floss.2007.9
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Success and Tragedy of FLOSS Commons: A Preliminary Classification of Sourceforge.net Projects

Abstract: Free/Libre and Open Source Software (FLOSS)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 5 publications
1
38
1
Order By: Relevance
“…Given the importance of this measure, we spent over a year figuring out measures of these concepts using SF project information, we classified the 2006 dataset based on our operationalization scheme, and we validated the classification by randomly sampling 300 projects and manually reviewing their project pages to make sure they indeed were correctly classified. We published a paper on this process (English and Schweik 2007) and Wiggins and Crowston (2010) independently verified our results.…”
Section: Methodssupporting
confidence: 67%
“…Given the importance of this measure, we spent over a year figuring out measures of these concepts using SF project information, we classified the 2006 dataset based on our operationalization scheme, and we validated the classification by randomly sampling 300 projects and manually reviewing their project pages to make sure they indeed were correctly classified. We published a paper on this process (English and Schweik 2007) and Wiggins and Crowston (2010) independently verified our results.…”
Section: Methodssupporting
confidence: 67%
“…The extent to which an open 53 source project is successful has often been evaluated empirically 54 by measuring endogenous characteristics, such as the amount of 55 developer activity, the number of developers, or the size of the pro-56 ject (Crowston et al, 2006;Godfrey and Tu, 2000;Robles et al, 57 2003). As an example, a thorough study of Sourceforge.net (a pop-58 ular repository of more than 200,000 open source projects) con-59 cluded that the majority of projects housed there should be 60 considered ''tragedies" by virtue of their failure to initiate a steady 61 series of releases (English and Schweik, 2007). This work extends and expands the previous study in two ways.…”
mentioning
confidence: 56%
“…Finally, other researchers have 138 created 5 categories for the overall SourceForge site, based on dy-139 namic growth attributes, and using the terms ''success" and ''trag-140 edy" within the FLOSS development. Again, it has been shown that 141 some 50% of the FLOSS projects should be considered as tragedies 142 (English and Schweik, 2007 based on Halstead's software science (Hamer and Frewin, 1982; 322 Shen et al, 1983 and per repository, to summarize the evolution of these attributes.…”
mentioning
confidence: 99%
“…A closed process, performed by a small group of developers, has some commonalities with traditional software development. Major differences appear when a FLOSS project either never leaves this initial stage, as documented for a large majority of the projects hosted on SourceForge [22]; or when it leverages a "bazaar", i.e. a large and increasing amount of developers.…”
Section: Case Studiesmentioning
confidence: 99%